Academy Awards Speeches Reflect Social Status, Cinematic Roles, and Winning Expectations. (June 2018) - Markowitz, David M.
An analysis of Academy Awards acceptance speeches revealed that social status is indicated through pronouns. Speeches from high status movie directors contained fewer self-references than relatively low status actors. Directors also communicated analytically compared with actors, who told stories and communicated narratively. A post hoc analysis revealed that unexpected award winners communicated more positively than those who were expected to win. The analyses emphasize the importance of replications in the social sciences and extending social and psychological phenomena to new settings.